ANALYSIS OF TYPES AND REASONS INDONESIAN-ARABIC CODE-SWITCHING BY SOCIOLINGUISTICS APPROACH - Sakti, Pratiwi (Jurnal TAMBORA, 2020)
The background of this research is to Investigate the types and reasons of IndonesianArabic code-switching in Indonesian community, especially in the Arabic Department. Itaims at investigating the types, syntactic categories, and reasons of Indonesian-Arabiccode-switching. The writer uses both quantitative and qualitative methods. It is countingand analysing the discourses between lecturer and students in the class. The population is80 students and the sample is limited on 34 students who have educational backgroundfrom Islamic institutional school. The length of meeting is 138.92 minutes with 35 topicdiscourses then sorted becoming 50 corpuses. The result of this study shows that in termof types of Indonesian-Arabic code-switching inter-sentencial is the most dominant of alltypes code-switching. It comprises 50% of the data. In term of Arabic syntactic wordcategories, noun occupies the first level. It comprises with 63 nouns with 38.41percents.In term of reason, repetition for clarification and emphasize the message are the mostdominant than others. It comprises 20-83%. The result of questionnaires shows that habitis the dominant reason of code-switching happens. The impact of this research is used forthe language teacher to allow their students switching the nationalto local language, viceversa, to absolve students expressing themselves through language learning methodsusing localization context.